A SYSTEM DESIGN OF A SOLAR AND GEOTHERMAL HYBRID POWER PLANT FOR FLORES ISLAND - Yakana Berian, Zagy
Indonesia is blessed with abundant geothermal energy potential. Flores Island for its geothermal energy potential has been declared as a Geothermal Island vis-à-vis the Minister of Energy and Mineral Resources of the Republic of Indonesia through article ESDM No. 2268/30/MEM/2017. Furthermore, solar energy potential in Flores Island has been recorded as much as 5 to 6 kWh/m2/day. As of today, electricity peak demand in Flores Island is served by a system of diesel-electric power plants. Hence, there is an opportunity to design and implement a hybrid geothermal and solar power plant for Flores Island. Based on existing geothermal fluid characteristics in Flores Island, a hybrid power plant is designed to comprising of a single flash geothermal power generation, a solar collector system with parabolic trough collectors (PTC) either in an East–West (E–W) or a North–South (N–S) alignment, and a thermal energy storage (TES) system with synthetic oil for heat transfer fluid (HTF) and a mixture of salts for storing thermal energy. The operation of the hybrid power plant is designed based on the result of the electricity load study for Flores Island. Solar energy potential for Flores Island is predicted by combining clear sky model empirical formulas and 2017–2019 sunshine duration data in Frans Lega Weather Station provided by BMKG (Meteorology, Climatology and Geophysics Agency). Steady mass and energy balance analyses via Aspen HYSYS were performed to obtain electric power generation capacity for each stand-alone geothermal power plant and hybrid power plant. In addition, a comparison of carbon dioxide emission from the same capacity of a diesel-electric power plant, a stand-alone geothermal power plant, and a hybrid power plant is presented. The hybrid power plant is designed to have a solar collector system with a N–S alignment PTC system which daily average solar irradiation is predicted to be 5.5 kWh/m2/day and a TES volume of 3,000 m3. The land area to be cleared for the solar collector system is estimated as 3 hectares (7.5 acres). For a steam turbine inlet pressure of 10 bar.a, a condenser pressure of 0.08 bar.a and 1,215 operation hours per year, the hybrid power plant is capable of producing 5,450 MWh/year of electric energy. In addition, the carbon dioxide emission reduction for a stand-alone operation and a hybrid operation are 86% and 93%, respectively, compare to that of a diesel-electric power plant.